An Analysis of Ju Xian in Movie Farewell My Concubine - Ruomei, Fu (Humaniora, 2014)
As the main female character in movie "Farewell My Concubine", Ju Xian was a brave, smart, worldly-wise but kindhearted woman. Even though she was a prostitute, she was longing for an ordinary life. She loved Xiao Lou, moreover, in order to engross Xiao Lou, she even tried to drive a wedge between Die Yi and Xiao Lou. She used her wisdom to save and protect Xiao Lou, but on the other hand, she was also the one who destroyed Xiao Lou and her own life. Article tried to through close reading analyze the character of Ju Xian and her relationships with Die Yi and Xiao Lou. Article revealed the inescapable tragic fate of Ju Xian.